Pengaruh Metode Pemberian ASI Eksklusif pada Ibu Bekerja secara WFH terhadap Status Gizi Bayi Masa Pandemi COVID-19: Metode ASI Eksklusif Ibu WFH terhadap Status Gizi Bayi - Adi Iskandar; Megah Stefani (Universitas Airlangga, 2022)
Background: Food intake, exclusive breastfeeding, and nutritional adequacy can affect normal nutritional status in children, especially during the first 1000 days of life. Objectives: Analyzing the effect of the exclusive breastfeeding method on the nutritional status of infants in Work From Home (WFH) working mothers Methods: The study was conducted quantitatively descriptively with a cross-sectional study design. Research respondents were selected mothers during the Covid-19 pandemic (PSBB or PPKM levels 3-4, namely from April 2020 to October 2021) who provided exclusive breastfeeding, and respondents worked under the WFH scheme. Respondents totaled 27 people who were divided into direct-breastfeeding (DBF) and mixed-feeding (MF) groups. Respondents have selected purposively sampling. meetings online namely by using platforms, namely Whatsapp and Zoom. Results: Significant relationship between exclusive breastfeeding methods with a weight-for-height z score (WHZ) (P = 0.031; R = -0.417) and a bmi-for-age z score (BAZ) (P = 0.044; R = -0.391), In addition, a significant difference was found between the mean of the DBF and MF groups on the WHZ (P=0.031) and WHZ (P=0.044) with the mean nutritional status of MF on the BB/TB or BB/PB index of 0.490. ± 0.970SD (at risk of overweight). Conclusions: Exclusive breastfeeding method has a significant relationship with normal baby weight. In addition, there are significant differences in the nutritional status of infants between the DBF and MF breastfeeding methods. babies with the MF method tend to be at risk of more nutrition. Mothers who work WFH are expected to maximize exclusive breastfeeding for babies, especially with the DBF breastfeeding method. In addition, the researchers hope that this research can serve as an advocate for the draft government regulation regarding 6 months of maternity leave to maximize exclusive breastfeeding for babies.